Displacing Natives: The Rhetorical Production of Hawai'i - Wood (Rowman & Littlefield Publishers, 1999)
This insightful study examines the strategies used by outsiders to usurp Hawaiian lands and undermine indigenous Hawaiian culture. Drawing upon historical and contemporary examples, Houston Wood investigates the journals of Captain Cook, Hollywood films, commercialized hula, Waikiki development schemes, and the appropriation of Pele and Kilauea by haoles to explore how these diverse productions all displace Native culture. Yet, the author emphasizes the voices that have never been completely silenced and can be heard asserting themselves today through songs, chants, literature, the internet, and the Native nationalist sovereignty movement. This impassioned argument about the linkages between textual and physical displacements of Native Hawaiians will engage all readers interested in Pacific literature and postcolonial studies.